Pengaruh Kompensasi dan Beban Kerja Terhadap Kinerja Pegawai Honorer dengan Motivasi Sebagai Variabel Intervening pada Sekretariat Daerah Kota Solok - Yulianis Yulianis; Yulasmi Yulasmi; Zefriyenni Zefriyenni (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The background of this study is based on the phenomenon of low performance of honorary employees which is allegedly influenced by lack of compensation and unbalanced workload. This study aims to analyze the effect of compensation and workload on the performance of honorary employees with work motivation as an intervening variable in the Solok City Regional Secretariat. This study uses a quantitative method with a survey approach, where data is collected through the distribution of questionnaires to 103 honorary employees who are the research samples. The data analysis technique used is Structural Equation Modeling (SEM) to test the relationship between the research variables. The results of the study indicate that compensation has a positive and significant effect on work motivation and employee performance. In contrast, workload shows a negative influence on work motivation but is not significant on employee performance. Additionally, work motivation is proven to be a significant intervening variable in mediating the effect of compensation on the performance of honorary employees. This study implies that increasing compensation can enhance employee motivation and performance, while excessive workload may decrease work motivation